Seizure precipitated during long haul flight - Devkota, AR; Karki, AR (Journal of Institute of Medicine Nepal, 2011)
We report three diagnosed cases of epilepsy under medication that were on long haul flight from Kathmandu to different destinations in USA with different clinical outcomes during flight. The first case had brief seizure like episode during flight and was given oral benzodiazepine. The second case was put on prophylactic oral benzodiazepine to induce sleep and reduce seizure threshold and had an uneventful flight. The third case developed generalized tonic clonic seizure and was managed accordingly. Key words: Epilepsy; long haul flight; seizure. DOI: http://dx.doi.org/10.3126/joim.v32i3.4962 Journal of Institute of Medicine, December, 2010; 32:3 59-61